Network dynamics of tourism development in South Korea. Issue 11 (24th July 2018) - Kim, Young-Rae; Scott, Noel
Abstract : This study utilizes network analysis to trace the evolution in the organizations of tourism development during South Korea's transition from a developing to a developed country spanning the period from 1945 to 1999. This is studied by examining changes within a network of organizations as their means and objectives evolve. Data are drawn from news articles that deal with tourism and development from 1945 to 1999, and coded into organizations, development-related means, and objectives. Two-mode and a one-mode metric network analysis and correspondence analysis of coded data were undertaken. The results show the dynamic nature of networks interacting among organizations along with their means and objectives. Furthermore, this study states that the "social embeddedness" of the tourism network became stronger over time, leading to further development opportunities.